The Effect of Head Orientation on Perceived Gaze Direction: Revisiting Gibson and Pick (1963) and Cline (1967) - Moors, Pieter; Verfaillie, Karl; Daems, Thalia; Pomianowska, Iwona; Germeys, Filip (Frontiers in Psychology, 2016)
Two biases in perceived gaze direction have been observed when eye and head orientation are not aligned. An overshoot effect indicates that perceived gaze direction is shifted away from head orientation (i.e., a repulsive effect), whereas a towing effect indicates that perceived gaze direction falls in between head and eye orientation (i.e., an attraction effect). In the sixties, three influential papers have been published with respect to the effect of head orientation on perceived gaze direction (Anstis, Mayhew, & Morley, 1969; Cline, 1967; Gibson & Pick, 1963). Throughout the years, the results of two of these (Cline, 1967; Gibson & Pick, 1963) have been interpreted differently by a number of authors. In this paper, we critically discuss potential sources of confusion that have led to differential interpretations of both studies. At first sight, the results of Cline (1967), despite having been a major topic of discussion, unambiguously seem to indicate a towing effect whereas Gibson and Pick’s (1963) results seem to be the most ambiguous, although they have never been questioned in the literature. To shed further light on this apparent inconsistency, we repeated the critical experiments reported in both studies. Our results indicate an overshoot effect in both studies.